2020
DOI: 10.1101/2020.09.06.285320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase precession in the human hippocampus and entorhinal cortex

Abstract: Knowing where we are, where we have been, and where we are going is critical to many behaviors, including navigation and memory. One potential neuronal mechanism underlying this ability is phase precession, in which spatially tuned neurons represent sequences of positions by activating at progressively earlier phases of local network theta (~5-10~Hz) oscillations. Phase precession may be a general neural pattern for representing sequential events for learning and memory. However, phase precession has never be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 102 publications
0
16
0
Order By: Relevance
“…Phase precession describes the phenomenon whereby the firing of a hippocampal 'place cell' precesses systematically from later to earlier phases of the underlying local field potential (LFP) theta oscillation as the animal advances across the cell's 'place field' (Huxter et al, 2003; (O'Keefe & Recce, 1993;Skaggs et al, 1996). Phase precession has also recently been confirmed in humans (Qasim et al, 2020).…”
Section: Significance Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase precession describes the phenomenon whereby the firing of a hippocampal 'place cell' precesses systematically from later to earlier phases of the underlying local field potential (LFP) theta oscillation as the animal advances across the cell's 'place field' (Huxter et al, 2003; (O'Keefe & Recce, 1993;Skaggs et al, 1996). Phase precession has also recently been confirmed in humans (Qasim et al, 2020).…”
Section: Significance Statementmentioning
confidence: 99%
“…In rodents, theta sequences are necessary for maintaining internally generated place fields when external cues are held constant (Wang et al, 2015), and for non-spatial event sequencing (Terada et al, 2017), suggesting that they may play a larger role in sequential processing beyond spatial cognition. Theta sequences have also been associated with goal planning and prediction (Gupta et al, 2012;Wikenheiser & Redish, 2015) and phase precession has been associated with non-spatial forms of sequential processing in both rodents (Pastalkova et al, 2008;Royer et al, 2012) and humans (Heusser et al, 2016;Qasim et al, 2020). In humans the hippocampus is involved in both episodic memory processes and thinking about the future (Schacter et al, 2007), and theta sequences may therefore have a fundamental role in these processes Jaramillo & Kempter, 2017;Terada et al, 2017;Wang et al, 2015).…”
Section: ……Figure 7 Here……………………………………………………………………………mentioning
confidence: 99%
“…Recent findings in animal models have also demonstrated that the precise temporal spiking of single cells in relation to background local field potential (LFP) oscillations is likely to be functionally important for both low-level plasticityrelated processes and for high-level cognition that depends on sequential processing mechanisms (Buzsáki, 2015;Buzsáki and Tingley, 2018;Drieu and Zugaro, 2019). While these synchronizing phenomena appear to occur in humans (Liu et al, 2019;Qasim et al, 2020) they cannot readily be investigated with non-invasive techniques. Thus, although MEG and EEG studies provide important correlational evidence that disturbed network synchrony is likely associated with poor performance across a range of cognitive domains, direct evidence that these phenomena are causally linked is difficult to obtain with these techniques alone.…”
Section: Eeg and Meg Studies In Individuals With Schizophreniamentioning
confidence: 99%
“…To analyze LFP phase precession, LFP phase in the theta bands was unwrapped such that the resulting phase is monotonic instead of cyclic (Mizuseki et al, 2009; Qasim et al, 2020). For each spike, we assigned the corresponding unwrapped LFP phase via nearest neighbor interpolation.…”
Section: Supplemental Informationmentioning
confidence: 99%
“…The precise relationship between theta phase and neuronal firing reflects a temporal code that may support communication across regions and organize ensemble activity into sequences (Mizuseki et al, 2009; O’Keefe and Recce, 1993; Skaggs et al, 1996). In contrast to rodents, primate studies have consistently found a lack of continuous theta oscillations either during virtual navigation or real world locomotion (Ekstrom et al, 2005; Talakoub et al, 2019), but spike-LFP phase coding appears to be conserved to some extent, at least in humans (Jacobs et al, 2007; Qasim et al, 2020).…”
Section: Introductionmentioning
confidence: 98%